Tetrahydrofuran hydroperoxide mediated synthesis of Prussian blue nanoparticles: A study of their electrocatalytic activity and intrinsic peroxidase-like behavior - Pandey P.C.; Pandey A.K. (My University, 2025)
We report herein, tetrahydrofuran hydroperoxide (THF-HP) mediated conversion of potassium ferricyanide into Prussian blue nanoparticles (PBNPs). The new process allows controlled conversion of single precursor (i.e., potassium ferricyanide) into water dispersible PBNPs that demonstrates potential viability for use in both homogeneous and heterogeneous catalysis. The typical process involves the mixing of optimum concentrations of potassium ferricyanide and tetrahydrofuran hydroperoxide resulting into the formation of PBNPs under ambient conditions as characterized by UV-Vis spectroscopy, atomic force microscopy, transmission electron microscopy, XRD and cyclic voltammetry. The as synthesized PBNPs shows wide practical applications i.e. (1) homogeneous electrocatalysis of glutathione (GSH), (2) peroxidase-like catalytic activity for H2O2 detection, (3) colorimetric determination of GSH based on competitive reaction of o-dianisidine and GSH with H2O 2, (4) electrocatalytic reduction of lipid hydroperoxides with better selectivity and sensitivity. The electrocatalytic and peroxidase mimetic abilities of these PBNPs promise a strong impact on practical biomedical devices. © 2014 Elsevier Ltd.